Susceptibility Vessel Sign in Relation With Time From Onset to Magnetic Resonance Imaging. Issue 5 (8th April 2021) - Soize, Sebastien; Manceau, Pierre-François; Gauberti, Maxime; Herbin, Thibault; Zuber, Mathieu; Pierot, Laurent; Touzé, Emmanuel
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: In acute ischemic stroke, the susceptibility vessel sign (SVS) on T2* MR-sequence witnesses the red blood cell content of the clot. Although clot composition strongly depends on its age in vitro, the relationship between SVS and time has not been studied. In this study, we evaluated whether the presence of SVS was related to the time from symptom onset. Methods: We retrospectively analyzed our institutional registry of patients with acute stroke between November 2007 and June 2018. We included patients with an ischemic stroke confirmed by diffusion-weighted imaging magnetic resonance imaging within 8 hours from symptom onset caused by M1 or M2 occlusion and with interpretable T2*-weighted images. We compared clinical and imaging variables among SVS+ and SVS− patients. Time from onset was split into tertiles. Independent markers of SVS+ were identified using multivariable logistic regression. The probability of being SVS+ given time from symptoms onset was modeled using Probit regression. Results: Among the 608 patients included, 433 (71.2%) were SVS+. The odds of being SVS+ increased with time from symptom onset ( P trend=0.005). In the multivariable analysis, factors independently associated with a SVS+ were symptom onset to magnetic resonance imaging ([130–180 min] odds ratio [OR], 1.62 [95% CI, 1.03–2.53]; [>180 min] OR, 3.14 [95% CI, 1.92–5.12]), type of magnetic resonance imaging-scanner (OR, 2.83 [95% CI, 1.82–4.41]), cardioembolic cause (OR, 1.51 [95% CI, 1.02–2.24]), and baseline National Institutes of Health Stroke Scale (OR, 1.05 [95% CI, 1.01–1.08]). The probability of being SVS+ increased with time from symptom onset ( P =0.004): around 60% at 1 hour, 70% at 3 hours, 80% at 6 hours, and 90% at 8 hours. Conclusions: In acute ischemic stroke, the presence of SVS depends on time from onset to imaging.